A new ecology : systems perspective - Jrgensen, Sven Erik, 1934- (Elsevier, 2007)
The diversity of nature's flora and fauna is staggering, and it is human nature to wonder how to explain the diversity, adaptability and beauty of the world that surrounds us. How can we explain the interactions between matter and energy that lead to the abiotic and biotic web of life on earth? These questions demand increasingly accurate answers as environmental managers endeavor to meet steeper sustainability benchmarks set by political agendas. This book presents an overview of the systems-based, thermodynamic properties that underpin this natural growth and development, and explains the underlying ecosystem properties that can explain the environment's response to natural perturbations and human interventions.